Efficient dealkalization of red mud and recovery of valuable metals by a sulfur-oxidizing bacterium - Zhang, Duo-rui; Chen, Hong-rui; Xia, Jin-lan; Nie, Zhen-yuan; Zhang, Rui-Yong; Pakostova, Eva (Frontiers in Microbiology, 2022)
Red mud (RM) is a highly alkaline polymetallic waste generated via the Bayer process during alumina production. It contains metals that are critical for a sustainable development of modern society. Due to a shortage of global resources of many metals, efficient large-scale processing of RM has been receiving increasing attention from both researchers and industry. This study investigated the solubilization of metals from RM, together with RM dealkalization, via sulfur (S0) oxidation catalyzed by the moderately thermophilic bacterium Sulfobacillus thermosulfidooxidans. Optimization of the bioleaching process was conducted in shake flasks and 5-L bioreactors, with varying S0:RM mass ratios and aeration rates. The ICP analysis was used to monitor the concentrations of dissolved elements from RM, and solid residues were analyzed for surface morphology, phase composition, and Na distribution using the SEM, XRD, and STXM techniques respectively. The results show that highest metal recoveries (89% of Al, 84% of Ce, and 91% of Y) were achieved with the S0:RM mass ratio of 2:1 and aeration rate of 1 L/min. Additionally, effective dealkalization of RM was achieved under the above conditions, based on the high rates (> 95%) of Na, K, and Ca dissolution. This study proves the feasibility of using bacterially catalyzed S0 oxidation to simultaneously dealkalize RM and efficiently extract valuable metals from the amassing industrial waste.